1995
DOI: 10.1523/jneurosci.15-08-05560.1995
|View full text |Cite
|
Sign up to set email alerts
|

Repeated confocal imaging of individual dendritic spines in the living hippocampal slice: evidence for changes in length and orientation associated with chemically induced LTP

Abstract: Using confocal microscopy in conjunction with microdrop application of Dil, we have imaged and measured individual dendritic spines of living hippocampal CA1 pyramidal neurons in acute brain slices, before and approximately 3 hr after induction of long-term potentiation by chemical means. Statistical analysis of changes in the length of individual spines, and comparison with results of Monte Carlo simulations, suggests that two forms of structural change occur in chemically induced long-term potentiation: grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 112 publications
(122 reference statements)
4
126
0
Order By: Relevance
“…There has been debate regarding the magnitude and time course of structural changes during LTP (Desmond and Levy, 1983;Hosokawa et al, 1995;Sorra and Harris, 1998;Engert and Bonhoeffer, 1999;Maletic-Savatic et al, 1999;Toni et al, 1999;Ostroff et al, 2002;Lang et al, 2004;Matsuzaki et al, 2004;Okamoto et al, 2004). Here, we briefly drive bursting of endogenous synaptic activity in organotypic hippocampal slices to produce synaptic enhancement that mimics LTP (Otmakhov et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There has been debate regarding the magnitude and time course of structural changes during LTP (Desmond and Levy, 1983;Hosokawa et al, 1995;Sorra and Harris, 1998;Engert and Bonhoeffer, 1999;Maletic-Savatic et al, 1999;Toni et al, 1999;Ostroff et al, 2002;Lang et al, 2004;Matsuzaki et al, 2004;Okamoto et al, 2004). Here, we briefly drive bursting of endogenous synaptic activity in organotypic hippocampal slices to produce synaptic enhancement that mimics LTP (Otmakhov et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic remodeling in hippocampus both accompanies long-lasting LTP (Hosokawa et al 1995;Engert and Bonhoeffer 1999;Toni et al 1999;Weeks et al 2001;Lang et al 2004;Matsuzaki et al 2004;Nägerl et al 2004) and occurs with several hippocampal-dependent associative learning and memory tasks (Geinisman et al 2001;Eyre et al 2003;Leuner et al 2003;Rekart et al 2007). Stereological analyses of synapse density in the dentate gyrus molecular layer have shown that spine number begins to increase ∼3 h post-IA training, peaks by 6 h, then returns to baseline values by 72 h (O'Malley et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We also tested whether reagents that stimulate activity would alter spine motility. Application of N-methyl-D-aspartate (1-50 M; n ϭ 1 hippocampus, n ϭ 1 cortex) or ''potentiation'' medium containing tetraethylammonium (19) did not affect spine motility ( Fig. 5f; n ϭ 3 hippocampus, n ϭ 2 cortex).…”
Section: Gfp-labeled Cells In Acute and Cultured Slices Have Normal Mmentioning
confidence: 92%